Route of fire: Pregame rituals and emotional synchrony among Brazilian football fans - Dimitris Xygalatas; Vitor Leandro da Silva Profeta; Mohammadamin Saraei; Gabriela Baranowski-Pinto (Proceedings of the National Academy of Sciences, 2025)
Sporting events are powerful social phenomena that extend beyond the game itself, offering a unique lens to study collective emotional dynamics. We examine emotional alignment among football fans during a high-stakes match in Brazil, focusing on both the game and the preceding Rua de Fogo, a pregame ritual marked by chants, flares, and collective anticipation. Using wearable electrocardiographic (ECG) sensors to monitor heart rate patterns, we apply multidimensional recurrence quantification analysis to track group synchrony over time. We find that the Rua de Fogo, driven by its sensory-rich and ritualized interactions, elicited the highest levels of emotional synchrony, surpassing even key moments of the game. This synchrony was sustained across participants, including the driver of the team delegation bus, who was not physically engaged in the ritual. Our results demonstrate the importance of pregame rituals in enhancing shared emotional experiences, underscoring the broader appeal of sports as a cultural phenomenon. By identifying the mechanisms underlying emotional alignment, this work contributes to understanding how collective gatherings promote unity and shared identities, with implications extending to other domains, such as religious ceremonies, political rallies, and public celebrations.